PREREQUISITE TO UNDERSTANDING THE MECHANISMS OF DEVELOPMENT OF BREAST CANCER - R. R. Bakiev (Креативная хирургия и онкология, 2017)
The article presents data  on the  growth and development of breast tissue.  A detailed morphogenesis mammary gland,  occurring  in mammary epithelium  during  the  life of the woman with the changes of the stroma was presented.